Harmonization of Population Data Between BPS and Palembang City Disdukcapil Using an Agile-Based Dashboard - Inayah Utami; Muhammad Nasir (Universitas Budi Darma, 2026)
Population data play a strategic role in supporting regional development planning and evaluation, particularly in urban areas with high population density such as Palembang City. However, discrepancies between population data produced by the Central Statistics Agency (BPS) and the Population and Civil Registration Office (Disdukcapil), resulting from differences in de facto and de jure recording concepts, pose challenges for comprehensive population analysis and policy formulation. This study focuses on the harmonization and integration of population data from BPS and Disdukcapil into a unified analytical platform. A dashboard-based system developed using the Agile method is employed as a supporting tool to facilitate population data analysis and support data-driven decision-making in Palembang City. Population data were obtained from official BPS publications and Disdukcapil administrative records, supported by observations, interviews, and questionnaires. The results show that all system functionalities operated successfully based on black-box testing, achieving a 100% success rate across all test scenarios. The main contribution of this research lies in the harmonization of de facto and de jure population data, which improves data consistency and supports more effective population analysis for regional development planning.